The Discourse on Net Zero Emission 2060: Economy First or Environment First? - Fadlan, Muhammad Sainul; Zulfa, Alfiatus; Pratama, Muhammad Reyfald Putra Febrian (International Journal for Disaster and Development Interface, 2026)
Indonesia has committed to achieving Net Zero Emission (NZE) by 2060 at the latest. Behind this discourse, the reality is that Indonesia remains heavily dependent on fossil fuels, which account for 80% of its energy mix, sparking significant public debate. This situation positions the mass media to shape public perception. Various national mass media outlets will frame the NZE 2060 issue with narratives concentrating on either economic interests or environmental sustainability. The objectives of this research are to (1) identify the frames used by the mass media in reporting on NZE 2060, and (2) analyze the arguments in news media that frame economic interests versus environmental sustainability. This study employs a qualitative approach using Robert Entman's framing analysis model. It utilizes secondary data from national online news articles published between 2022 and 2025. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing. The discourse on Net Zero Emission (NZE) is often framed around issues of investment opportunities, transition costs, burdens on the state budget, and industrial growth, with dominant sources from the Government and business actors. In contrast, the environmental sustainability frame tends to highlight the climate crisis, disaster threats, and ecological disruptions, yet receives less coverage, with its voice primarily carried by academics and civil society organizations. Pragmatically, the narrative in the NZE 2060 news coverage predominantly highlights economic interests